1989
DOI: 10.1152/ajpendo.1989.257.5.e654
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sympathetic activity and norepinephrine release during mental challenge in humans

Abstract: Muscle sympathetic nerve activity (MSA; peroneal nerve) and arterial and femoral venous plasma norepinephrine (NE) were studied in 10 volunteers at rest, during a relaxation procedure (RELAX), and during two mental challenges, a word identification test (WIT) and a color word test (CWT). [3H]NE infusions were used to assess NE spillover to and clearance from plasma. Net NE overflow from the leg was calculated. RELAX reduced MSA and femoral venous NE concentrations. CWT increased blood pressure, cardiac output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
78
1
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 22 publications
11
78
1
1
Order By: Relevance
“…Throughout the mental arithmetic stress test, the subjects were urged to work more quickly and more accurately. 18,19 The cold pressor test was performed by immersing the left hand of the subject in ice water up to the wrist for 2 minutes. 20 MSNA was analyzed by visual inspection by a single investigator (R.M.B.).…”
Section: Microneurography Assessmentmentioning
confidence: 99%
“…Throughout the mental arithmetic stress test, the subjects were urged to work more quickly and more accurately. 18,19 The cold pressor test was performed by immersing the left hand of the subject in ice water up to the wrist for 2 minutes. 20 MSNA was analyzed by visual inspection by a single investigator (R.M.B.).…”
Section: Microneurography Assessmentmentioning
confidence: 99%
“…23 We cannot exclude the possibility that primary central factors also play a role in the increased sympathetic activation in POTS patients; however, it is of interest that the increase in sympathetic outflow in response to mental stress (a condition characterized by a central increase in sympathetic outflow that is not provoked by hypotension) is associated with an increase in both burst number and burst amplitude. 24,25 In contrast to the enhanced sympathetic burst activity in response to baroreceptor unloading in POTS patients, sympathetic nerve activity in the supine resting condition was characterized by a lower burst incidence. The lower probability of burst generation during a cardiac cycle at rest in POTS patients may be attributable to the following, acting alone or in combination: (1) increased resting blood pressure, (2) shorter cardiac interval, (3) lower-extremity sympathetic denervation, and (4) impairment of the central sympathetic burst generator.…”
Section: Nauseamentioning
confidence: 99%
“…One possible mechanism underlying the skeletal muscle vasodilatation and consequent decrease (lack of increase) in systemic vascular resistance would be a reduction in sympathetic (vasoconstrictor) nerve activity to skeletal muscle (MSNA). Previous studies, however, have reported both increases and decreases in MSNA during mental tasks (Delius, Hagbarth, Hongell & Wallin, 1972;Wallin, Delius & Hagbarth, 1973;Wallin, 1981;Anderson, Wallin & Mark, 1987;Hjemdahl, Fagius, Freyschuss, Wallin, Daleskog, Bohlin & Perski, 1989;Matsukawa, Gotoh, Uneda, Miyajima, Shionoiri, Tochikubo & Ishii, 1991). Within these studies, individual variability in both the direction and magnitude of MSNA responses has been noted frequently.…”
mentioning
confidence: 97%